2017
DOI: 10.9734/ajob/2017/33229
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parasites Infection of Resident Fish Species in a Tropical Reservoir

Abstract: This study detected, identified and determined the incidence of parasites present in and on Clarias gariepinus, Sarotherodon galilaeus, Oreochromis niloticus and Tilapia zillii in Ero reservoir, a tropical reservoir situated in Ikun-Ekiti, Nigeria. Fish species were randomly obtained from fishermen at the reservoir during the rainy season. Out of 55 fish samples examined, 17 (30.9%) fishes were invaded. 11(20.0%) were infected by Protozoans (Ciliates and Flagellates) and 6(10.9%) were infected by Metazoans (My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 2 publications
2
11
1
Order By: Relevance
“…Parasites have been known to cause changes in growth, behavioral changes which are negative in reaction and mechanical injury (Iwanowicz 2011). In this study, prevalence rate was low (9.8%) when compared to other reports on fish parasites in the tropics reservoir (Okoye et al 2014;Bedasso 2015;Oso et al 2017). In order to survive, reproduce and have access to food, parasite depends on their host ).…”
Section: Fish Parasites Recovered In the Reservoircontrasting
confidence: 58%
“…Parasites have been known to cause changes in growth, behavioral changes which are negative in reaction and mechanical injury (Iwanowicz 2011). In this study, prevalence rate was low (9.8%) when compared to other reports on fish parasites in the tropics reservoir (Okoye et al 2014;Bedasso 2015;Oso et al 2017). In order to survive, reproduce and have access to food, parasite depends on their host ).…”
Section: Fish Parasites Recovered In the Reservoircontrasting
confidence: 58%
“…Studies have shown that water pollution affects parasitism either positively or negatively. According to Oso et al (2017) [46] , when hosts (fish) of parasites are stressed as a result of natural and anthropogenic stressors, it reduces their ability to resist parasitic infections, therefore parasitism will increase. Akinsanya et al (2020) [5] also reported the destruction of plankton community through conventional fishing and other anthropogenic activities as a promoter of food competition which could contribute to either high or low prevalence of parasitic infection.…”
Section: Discussionmentioning
confidence: 99%
“…The public health issues caused by zoonotic parasites and the prevention of their transmission to humans and other animals are of great importance. Information on the occurrence, prevalence, and pathogenicity of fish parasites and diseases is essential in aquaculture production, as such information enables aquaculturists to apply correct prevention and control measures in their fish production and also provide useful information on their public health-related concerns (Oso et al, 2017). Since fish is an affordable and accessible source of animal protein for Nigerian families (Eric et al, 2018), the marketing of freshly captured live fish is common in the markets (Bimal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%